"This is the end, my only friend" Tomasza Beksińskiego wizja świata i (anty)wartości w felietonie "Fin de siecle" = "This is the end, my only friend" Tomasz Beksiński's vision of the world and (anti)values in the feuilleton "Fin de siecle" - Karczewska, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the paper is to present the world from the perspective of Tomasz Beksiński, music journalist and film translator, which was depicted in his feuilleton ?Fin de si?cle? written shortly prior to his suicidal death in 1999.
Keywords: Beksiński, Tomasz (1958-1999); felieton; Fin de siecle; intertekstualność; transtekstualność; feuilleton; intertextuality; transtextuality